2017
DOI: 10.1021/acs.jced.7b00299
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Properties, Viscosity, and Refractive Indices of Different Naringenin Solutions at Several Temperatures

Abstract: Thermophysical properties including densities and viscosities of naringenin in aqueous solutions of ethanol/1-propanol with alcohol concentrations of (24.00 to 40.00) mol•kg −1 have been measured as a function of concentration of naringenin at temperatures from (293.15 to 323.15) K and atmospheric pressure. Also, refractive indices for studied systems have been determined at 298.15 K. The measured data were used to calculate the apparent molar volume (V ϕ ), standard partial molar volume (V ϕ 0 ), partial mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…hydrophilic–hydrophobic interactions between the hydroxyl, carboxyl, and ether groups of the FA molecule and the alkyl group of the ethanol and 1-propanol molecules (negative contribution to volume); , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…hydrophilic–hydrophobic interactions between the hydroxyl, carboxyl, and ether groups of the FA molecule and the alkyl group of the ethanol and 1-propanol molecules (negative contribution to volume); , …”
Section: Resultsmentioning
confidence: 99%
“…Fourth, from Table , it can also be observed that the V ϕ0 values for FA decrease as the temperature of the aqueous ethanol/1-propanol solutions is raised. This may be due to the decrease in hydrophobic hydration at higher temperatures , and a release of a fraction of water molecules from the hydrophobic hydration layer, which leads to a negative contribution to V ϕ0 . A similar result was also observed by Ayranci et al for FA in methanol and by Yan et al for naringenin in an aqueous ethanol/1-propanol solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations